Exercise mediates the sex differences in adult visuospatial cognitive ability - Ruiqi Ruan; Junsheng Hong; Yan Huang; Fan Yuan; Xuehao Zhang; Yefei Mo; Tianxiao Hu; Tianxiao Hu; Yuhe Liu (Frontiers in Psychology)
BackgroundSex differences in visuospatial cognitive performance have been consistently documented, with males typically demonstrating superior performance in tasks requiring spatial processing. While multiple biological, psychological, and sociocultural factors have been proposed to explain these differences, the role of physical exercise as a potential mediator remains understudied. Given that females typically engage in less physical exercise than males globally, this study aimed to investigate whether exercise intensity serves as a mediating factor in the observed sex/gender differences in visuospatial cognitive ability.MethodsA total of 224 undergraduate students (112 men and 112 women) aged 18–25 years participated in a comprehensive battery of visuospatial cognitive tests, including assessments of mental rotation, spatial memory, and spatial navigation ability. Participants’ weekly exercise patterns were assessed using the validated Godin-Shephard Leisure-Time Physical Activity Questionnaire, with activities categorized into strenuous, moderate, and mild exercise. Mediation analyses were conducted using the PROCESS macro (Model 4) with 5,000 bootstrap iterations, controlling for spatial anxiety, sense of direction, and childhood spatial activity experience.ResultsMales significantly outperformed females across all visuospatial cognitive domains (all p < 0.05). Mediation analysis revealed that leisure time activity score significantly mediated sex/gender differences in visuospatial cognitive ability, with indirect effects ranging from 20 to 34% of the total effect. When examining exercise intensity separately, strenuous exercise emerged as the primary mediator, particularly in mental rotation (indirect effect = 0.073, 95% CI [0.021, 0.134]) and spatial memory tests (forward span: indirect effect = 0.073, 95% CI [0.017, 0.147]; backward span: indirect effect = 0.069, 95% CI [0.009, 0.143]). The mediating effect of strenuous exercise was more pronounced in tasks with higher cognitive demands.ConclusionPhysical exercise, particularly strenuous exercise, partially mediates sex differences in visuospatial cognitive abilities among young adults. These findings suggest that promoting increased participation in strenuous physical activities among women may help reduce gender disparities in visuospatial cognition. However, the cross-sectional nature of this study precludes causal inferences, and future longitudinal or intervention studies are needed to confirm these relationships.